Economic and Legal Views of Depletion Premium in the Extraction of Petroleum Resources - Arsegianto, Arsegianto (Indonesian Journal of International Law, 2007)
Production Sharing Contract (PSC) has become the model of contract of th upstream petroleum sector in Indonesia. Based on Act No. 22 Year 2001, the activity in oil and gas in upstream sector can run if there a cooperation contract whose it can be the production sharing contract or another form of cooperation contract, that it can bring more the profit to the state. In the management of the natural resources like oil and gas, it must have the allocation of the usage costs or depleting premium for replacing the taking of the a unit whose caused a lot of lost of the opportunity of a future natural resources, as a part of sustainable development. This article is trying to give a concept of depletion premium in a cooperation contract that can be realised by the government by the control at upstream oil and gas business, as stated in Article 33 constitution 1945.